Pelatihan Budidaya dan Aklimatisasi Anggrek secara In Vitro: Upaya Meningkatkan Ekonomi di saat Pandemi Covid 19: Orchid Cultivation and Acclimatization Training in Improving the Economy during the Covid 19 Pandemic - Khusnul; Kartawan Kartawan; Egi Nuryadin (Politeknik Negeri Jember, 2022)
The prosperous fertile agricultural group in KP ponyo RT 01 RW 10 Tawangbanteng Village, Sukaratu District, Tasikmalaya Regency mobilized the community of their farmer groups to try to rise from adversity due to the Covid-19 pandemic. One of the programs or activities of the prosperous fertile farmer group community is the cultivation of orchids. However, their cultivation is still conventional so that productivity is low and marketing is still done on a local sub-district scale. The purpose of this service is to increase the productivity of seeds in quantity and quality with in vitro and in vivo culture techniques, as well as the productivity of increasing skills and income for the community of prosperous fertile farmer groups. The methods used consisted of surveys, counseling and training on cultivation, marketing of seeds and orchids in pots. The results of the service activities are increasing community knowledge and skills related to in vitro orchid cultivation, orchid acclimatization, orchid maintenance, and orchid marketing..